Desempenho de cultivares, produtividade e qualidade de beterraba em sistemas de cultivo - Coutinho, Pablo Wenderson Ribeiro (2016)
The objective of this study was to evaluate the physicochemical and biometric characteristics and productivity of beet cultivars, in addition to productivity and quality characteristics of beet and chicory on the basis of management of stubble and intercropping establishment time. Thus, two experiments were conducted in a randomized block design, with four replications. In the first experiment the cultivars were Maravilha, Merlot, Kestrel, Itapuã 202, Chata do Egito e Tall Top Early Wonder. Was evaluated plant height, leaf number, crown projection, diameter and length of root, root shape index, root weight, leaf mass and productivity of beet, in addition to the root quality characteristics, such as soluble solids , titratable acidity, ratio, hydrogen potential and anthocyanin content. The second experiment was conducted in the same design, and used the statistical analysis in factorial 2 x 5 and 2 x 8. The first factor consisting of the management of stubble (with and without incorporation of straw velvet bean-gray) and the times of establishment of the consortium and beet monoculture with chicory (0, 7, 14 and 21 days after transplanting beet); and the second factorial consists of the management of stubble (with and without incorporation) and the chicory cultivation in monoculture and associated with beetroot in the same periods in order to isolate possible planting effect. The assessment in this experiment found the same first requirements for the cultivation of beet, except projection cup, pastry sheets and anthocyanin content. As for the chicory were evaluated plant height, canopy projection, number of leaves, leaf area, fresh weight of aerial part and the calculation of UET. The results of the first experiment allow us to state that Maravilha, Itapuã 202, Chata do Egito and Tall Top Early Wonder presented the highest yields and root weight. However, in the general context it has been observed that cultivars behave differently for each variable analyzed. For root quality characteristics no difference was observed for pH and soluble solids. The cultivar Chata do Egito had the lowest acidity compared to the Tall Top Early Wonder and Kestrel, already for ratio, the same cultivars have the greatest results. Cultivars that have the highest content of anthocyanins was Merlot, Kestrel and Chata do Egito. The cultivar that showed the best quantitative and qualitative characteristics was Chata do Egito. In the second experiment the presence of chicory interferes in the productivity of beet when the transplant was carried out both at the same time. Thus it is clear that the consortium's efficiency depends on the temporal and spatial complementarity between cultures. For the physicochemical characteristics of the beet was no statistical difference in the pH when evaluated the effects of management of stubble and the establishment of the time. For soluble solids occurred only difference to the time of establishment. The management of stubble and establishment of time influenced the ratio of beet. The fresh weight of chicory was influenced by the management of stubble and the time of establishment. The efficiency of land use at all times of intercropping and both managements of straw were viable